2013
DOI: 10.1007/s00280-013-2142-9
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of pemetrexed as first-line treatment in elderly (≥75) non-squamous non-small-cell lung cancer: Kyoto Thoracic Oncology Research Group Trial 0901

Abstract: Although this study did not meet our primary endpoint, pemetrexed showed favorable antitumor activity with mild toxicity in elderly patients with non-squamous NSCLC. Further investigations of pemetrexed in this population are warranted (UMIN-CTR number, 000002452).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Detailed toxicity data were not available for all patients because of the retrospective nature of the study, and were, therefore, not considered in our analysis. However, treatment with pemetrexed in elderly patients with MPM was generally feasible, confirming previous data in MPM and other cancers (Ceresoli et al , 2008; Gridelli et al , 2012; Gervais et al , 2013; Kim et al , 2013). …”
Section: Discussionsupporting
confidence: 86%
“…Detailed toxicity data were not available for all patients because of the retrospective nature of the study, and were, therefore, not considered in our analysis. However, treatment with pemetrexed in elderly patients with MPM was generally feasible, confirming previous data in MPM and other cancers (Ceresoli et al , 2008; Gridelli et al , 2012; Gervais et al , 2013; Kim et al , 2013). …”
Section: Discussionsupporting
confidence: 86%
“…A meta‐analysis of 2671 patients with NSqNSCLC and good PS revealed that the effect of pemetrexed on overall survival did not differ between younger and older patients when cut‐off ages of 65 or 70 years were used . Moreover, in elderly patients aged ≥ 75, pemetrexed was reported to be safe and effective . Pemetrexed is very effective and causes little toxicity in patients with NSqNSCLC, even in elderly populations .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in elderly patients aged ≥ 75, pemetrexed was reported to be safe and effective . Pemetrexed is very effective and causes little toxicity in patients with NSqNSCLC, even in elderly populations . However, there is a lack of information about the optimal treatments for elderly patients with locally advanced NSqNSCLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gridelli et al [17] put forward that the median PFS and OS for elderly patients with stage IIIB/IV NSCLC are 4.5 months and 3.3 months, respectively. Kim et al [18] have found that median PFS and OS of elderly NS-NSCLC patients who received pemetrexed as first-line treatment are 3.3 and 17.5 months, respectively. In the present study, OS, PFS, and DCR of all patients receiving pemetrexed-based treatment in first-line setting was 15.6 months, 4.5 months, and 67.3%, separately, supporting favorable antitumor activity of pemetrexed-based treatment in elderly patients.…”
Section: Discussionmentioning
confidence: 99%